Pengaruh Penetapan Harga Pokok Produksi Dan Strategi Pemasaran Terhadap Tingkat Pendapatan Usaha Mikro Kecil Menengah (UMKM) - Triwidatin, Yuppy; Jamaludin , Ayi; Afif , M.Nur; Hurriyaturrohman , Hurriyaturrohman (Jurnal Akunida, 2022)
Micro, Small and Medium Enterprises or known as MSMEs have many roles in eradicating poverty, reducing unemployment, and increasing people's income so that they can be independent in supporting their economy. Therefore, the government continues to strive so that MSMEs in various regions can develop so as to support the economy of small communities by providing various facilities both in terms of funding, marketing, licensing and other supporting facilities. The presence of the industrial revolution 4.0 has the impact of intense competition, MSMEs must be able to overcome this challenge creatively, product innovation, marketing, product packaging, human resource development and technology. The MSME empowerment strategy can be pursued through the role of the Government in issuing fiscal and non-fiscal policies, the role of universities in carrying out services to educate and prosper the community and the role of stakeholders in encouraging MSMEs to be more independent and innovative. Research by Beginner Lecturers using university grant funds is focused on SMEs located in Ciawi Village, Bogor Regency, who are able to calculate the cost of production and are able to make plans in the budget for running a business.